159k views
0 votes
Which is equivalent

Which is equivalent-example-1
User Msvcyc
by
5.3k points

2 Answers

2 votes

Answer: Second option


(x^5y)^{(1)/(3)} = x^{(5)/(3)}y^{(1)/(3)}

Explanation:

By definition we know that:


a ^{(m)/(n)} = \sqrt[n]{a^m}

In this case we have the following expression


\sqrt[3]{x^5y}

Using the property mentioned above we can write an equivalent expression for
\sqrt[3]{x^5y}


\sqrt[3]{x^5y} = (x^5y)^{(1)/(3)}


(x^5y)^{(1)/(3)} = x^{(5)/(3)}y^{(1)/(3)}

Therefore the correct option is the second option

User Bindiya Patoliya
by
5.8k points
4 votes

Answer:


x^(5)/(3) y^(1)/(3)

Explanation:

This question is on rules of rational exponential

where the exponential is a fraction, you can re-write it using radicals where the denominator of the fraction becomes the index of the radical;

General expression


a^(1)/(n) =\sqrt[n]{a}

Thus
\sqrt[3]{x} =x^(1)/(3)

Applying the same in the question


\sqrt[3]{x^5y} =x^(5)/(3) y^(1)/(3)

=
x^(5)/(3) y^(1)/(3)

User Omar
by
5.8k points